Health Educators in Florida's County Public Health Departments: Frequency of and Perceived Confidence in Performing Entry-Level Competencies - Gwendolyn Matthews; Michelle Johnson Moore; Chudley Werch (University of North Florida, 2004)
The purpose of this study was to determine whether the activities of health educators in Florida's county health departments concur with the responsibilities and competencies for health educators that have been established by the National Commission for Health Education Credentialing (NCHEC, 2003). Fifty-three (68.8%) county public health department health educators completed a modified version of the Self-Assessment for the Health Education Specialist instrument (National Task Force, 1987) to determine the frequency and perceived confidence in performing entry-level health educator responsibilities. The data indicated that the entry-level responsibilities reflect the current health education practice in this group of health educators. The responsibility areas of planning and implementing health programs received the highest mean scores for frequency of performance (M=3.98, SD=0.66; M=3.88, SD=0.89, respectively) and perceived confidence level (M=4.13, SD=0.75; M=4.14, SD=0.90, respectively), whereas communicating and evaluating received the lowest mean scores for frequency (M=3.46, SD=0.94; M=3.49, SD=1.08, respectively) and perceived confidence level (M=3.86, SD=0.84; M=3.61, SD=1.11, respectively). A statistically significant positive correlation (p<.001) was found between frequency of performance and perceived confidence level for the mean scores of all seven responsibility areas. There were no statistically significant differences between health education and non-health education majors in their frequency and perceived confidence levels in performing the responsibilities, nor was there a statistically significant correlation between the years of experience and the frequency or perceived confidence level of performing the responsibilities. Implications for training needs of health educators in Florida's public health departments are discussed.